2022
DOI: 10.32535/jicp.v5i2.1677
|View full text |Cite
|
Sign up to set email alerts
|

Competitiveness of Indonesia’s Crude Palm Oil (CPO) in International Markets: Based on Database 2018

Abstract: As one of the largest CPO exporting countries in the world, Indonesia has a CPO production that continues to increase every year. Through this study, an analysis of the factors affecting Indonesia's CPO competition in the international market in recent years was carried out. The growth of export volume has a positive and significant influence on the competitiveness of Indonesia’s CPO in the international market, while the selling price and inflation in the main export destination countries show a negative and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Sustainability certification plays an essential part in the improvement of socio-economic and the eficiency of environmental palm oil production. So, if farmers can boost production efficiency while simultaneously enhancing quality, it has the potential to lower Indonesia's palm oil price, increase export amounts, and enhance the value of palm oil itself (Betrix, Fajri, & Rawung, 2022). Dahliani, Nurdialy, Relawati, and Abduh (2022) found that the well-being from farmers of oil palm in border regions reached a new normal.…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability certification plays an essential part in the improvement of socio-economic and the eficiency of environmental palm oil production. So, if farmers can boost production efficiency while simultaneously enhancing quality, it has the potential to lower Indonesia's palm oil price, increase export amounts, and enhance the value of palm oil itself (Betrix, Fajri, & Rawung, 2022). Dahliani, Nurdialy, Relawati, and Abduh (2022) found that the well-being from farmers of oil palm in border regions reached a new normal.…”
Section: Introductionmentioning
confidence: 99%